Contemporary Perioperative Analgesia in Total Knee Arthroplasty: Multimodal Protocols, Regional Anesthesia, and Peripheral Nerve Blockade - Drew, Jacob M.; Neilio, Jonathan; Kunze, Lisa (The Journal of Knee Surgery, 2018)
Perioperative care of the total knee arthroplasty (TKA) patient has evolved considerably over the past decade. Among the changes driving this evolution toward shorter hospitalization and accelerated rehabilitation have been regional anesthesia, peripheral nerve blockade, and multimodal analgesia protocols. These complementary techniques are increasingly supported by scientific evidence, though considerable uncertainty persists regarding the optimal combination of strategies. Continued refinement of technique and critical evaluation is trending toward greater characterization of the comparative effectiveness of myriad options. Contemporary interdisciplinary arthroplasty care teams have the opportunity to individualize the TKA patient's perioperative pain control to optimize not only the clinical outcome but also patient satisfaction.
Keywords: primary total knee arthroplasty; multimodal pain; peripheral nerve block; regional anesthesia; analgesia